IMMEDIATE IMPLANTS PLACED INTO INFECTED SOCKETS (Journal of Hama University, 2019)
It is already known that dental implants cannot  be placed in infected areas unless after at least six weeks and this was called delayed immediate implantation.This study made the opposite to the previous rule and we hope to get affirmative results with using different types of bone graft materials.Aims of research:Evaluation the effect of three calcium phosphate and palate rich plasma in bone absorption in the bone absorption in the immediate implantation in infected sockets.Materials and methods:The study included 20 cases of immediate implants placed into infected socketsThe sample was divided into two equal groups: the first group: 10 immediate implants plants with the use of three-calcium phosphate and 10 immediate implants with platelet rich plasma. The cases were monitored clinically and radically (1 month, 4 months, 12 months) of surgical work to assess the recovery.Results: it seemed like the bone absorption around the immediate implants with the use of three calcium phosphate less than it when the use of palate rich plasma with this implants in the infected sockets so it is advisable to use three calcium phosphate bone graft with the immediate implantation in the infected sockets instead of palate rich plasma